Convolutional Neural Network for Fashion Images Classification (Fashion-MNIST) - Shiun, Tang Jian; Yi, Tey Jia; Yu, Pu Jun; Xin, Por Jia; Yi, Voon Pei; Salam, Zailan Arabee Abdul (Journal of Applied Technology and Innovation, 2023)
Recognizing and classifying images is a significant research topic in the widely used computing technology nowadays—the computational vision. The common ways for classifying images and performing recognition tasks depend on deep learning, such as the Convolutional Neural Network (CNN). With the high impact resulting from Artificial Intelligence identified through the transformation in the fashion and apparel industry, it has then been realized that difficulty has been found in terms of understanding the work performed in the industry. In this research, it is aimed to focus on identifying the parameters that are able to affect the accuracy of the particular trained model for fashion image classification using deep learning in neural networks such as CNN with the Fashion MNIST dataset.